Comunicação do YouTuber brasileiro: aspectos não verbais, verbais e vocais - Quirino, José Henrique de Moura (2019)
Introduction: with the advancement of technology, a new type of communication has gained a lot of space, the virtual communication. The YouTube Platform is an example of space where it is possible to share ideals, knowledge and information. From this medium, the present research sought to investigate the communication of the YouTubers through three different groups of evaluating judges: one of users of the YouTube Platform, the audience for which it is basically intended, another for speech therapists and the third called general audience. Objective: to analyze, through different evaluators, the communication of the five Brazilian YouTubers with focus on nonverbal, verbal and vocal aspects. Method: The five Brazilian YouTubers that had more than 10 million subscribers in their respective YouTube video channels, four men and one woman, were selected. It was suggested that the evaluating subjects should watch at least the initial three minutes of each video. These videos were analyzed by three different groups of evaluating judges: one composed by speech-language pathologists; the second by the YouTube public, with individuals between the ages of 16 and 34 and the third was composed by the general public, with subjects aged 35 or over. To analyze the videos, a specific instrument was developed for the study based on the literature and the experience of the researchers. The instrument presented questions related to non-verbal, verbal and vocal aspects. Results: within the non-verbal aspects, according to the evaluating judges, the body posture of the YouTubers did not call attention, the gestures were used in moderation and according to the discourse and used above the body; the most detected facial expression was that of joy. The clothes did not attract attention, except YouTuber Whindersson Nunes who was shirtless. Within the verbal aspects the group of judges evaluators general public and speech audiologists considered the vocabulary informal and composed of swearing and slang, while the YouTube public considered formal and within the cultured norm. The speech was considered accelerated, but without problems of intelligibility. The vocal aspects had individual characteristics for each YouTuber, however the intensity of the voice was considered strong (speak loudly). The YouTubers have created a sense of credibility in the listeners and aroused interest, especially in the younger audience. Conclusion: in the evaluation of the communication of the five Brazilian YouTubers with the greatest number of hits on the respective Youtube channels, the highlight was for the expression of joy, the accelerated speech with intelligibility, the strong voice intensity and an informal vocabulary